Effect of Hot Water Extracts of Maqui Berry on Human Aortic Endothelial Cells Exposed to a Hyperglycemic Environment. (29th May 2020) - Martin, Keith
Abstract: Objectives: Impaired endothelial function is associated with many chronic vascular-related diseases including cardiovascular disease, inflammation, and diabetes. The antioxidant-rich Maqui berry ( Aristotelia chilensis ) has received increasing attention due to a variety of bioactivities including reduction of inflammation, control of blood glucose, and improvement of heart health, e.g., aortic endothelium, but corroborative research is needed. In the present study, we investigated the effects of aqueous Maqui berry extract (MBE) on nitric oxide (NO) production and oxidative stress (ROS) generation in human aortic endothelial cells (HAEC) alone or in a hyperglycemic environment with or without insulin. Methods: Sterile (0.22 um filtered) MBE was added to endothelial basal medium (5% v/v) alone or containing glucose (final concentration 600 mg/dL; 33.3 mM) and/or insulin (final concentration 100 nM) followed by addition to monolayers and incubation for 24 hours. Monolayers were then assayed for NO production via the Greiss reaction, ROS via the use of DCFH-DA, and viability using MTT. Results: We show that MBE may have increased ROS levels by 1.8-fold ( P < 0.05) compared to control cultures using the DCFH-DA assay but decreased by ∼13% in the presence of glucose with or without insulin. MBE also increased NO levels by 3-fold ( P < 0.05) compared to levels in control cultures. Glucose inclusion reduced NO by 15% and insulin reduced levels to that of control with or without glucose present. Viability, determined by MTT reduction, was not different between any of the groups. Conclusions: The results suggest that water-soluble components of MB may modulate NO production in a hyperglycemic and/or hyperinsulinemic microenvironment and potentially improve endothelial function, in part, via the potential vasorelaxation properties of NO. Funding Sources: School of Health Studies, University of Memphis.